P131 Lessons learnt from Patient Public Involvement. (30th June 2016) - Cochrane, Sarah; Clarke, Michael; Haskins, Jackie; Farmer, Lucinda
Abstract : Background/introduction: NHS England are clear that patients and carers should supported in their involvement to help shape NHS services. Patient public involvement (PPI) groups to determine patients' views can be used to plan and improve services. Aim(s)/objectives: To hold a patient focus group discussing expectations of an integrated GUM clinic and explore patient views regarding engagement with our service. Methods: A survey given to all patients assessed views on PPI. Interested patients were requested to complete contact details. 12 mixed sex patients confirmed to attend a 90 minute session at a local venue, facilitated by an independent lead. Topics were decided in advance. Responses were documented by clinicians. Results: 306 completed the survey: 89% agreed patient involvement is important. 65 left contact details. 5/12 confirmed participants attended the session; all were male. All stated they would participate in future PPI sessions, and would be agreeable if held within our clinic. Discussion/conclusion: The survey demonstrated that patients agree public involvement is beneficial. However, only a fifth agreed to be contacted for this project. The focus group provided valuable development suggestions including increasing bookable appointments and introducing online triage. Acceptability of holding groups within our clinic enables a financial saving compared to external venues. Adequate participant numbers remains a challenge, with further sessions achieving a similar 50% attendance. Suggestions include reducing time between survey and date of focus group. Increasing invited numbers would allow for high drop-out rates. Trialling targeted focus groups e.g. single sex or telephone interviews may improve patient acceptability.